Influência de resíduos de carvão vegetal e esterco de gado no desenvolvimento de mudas de faveira (Enterolobium barnebianum) - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
The production of seedlings includes stages that may require greater or lesser financial investments, such as fertilization. One way to minimize costs is to use organic materials that can be rich in nutrients and physically condition the substrate. Thus, the objective of this work was to evaluate the performance of faveira seedlings (Enterolobium barnebianum) in substrates composed of bovine manure and charcoal produced from segments of trunk and branches of Lacre. The experiment was carried out in a greenhouse, using a completely randomized experimental design, in a factorial scheme (5 x 5) and five replications. The study factors were: five doses of ground charcoal (0, 20, 40, 60 and 80 t ha-1) and five doses of bovine manure (0, 10, 20, 30 and 40 t ha-1). The evaluated characteristics were: shoot and root dry mass, the concentration of macro and micronutrients in the shoot and the chemical attributes of the soil. The application of doses above 40 t ha-1 of charcoal negatively affected plant growth and decreased the concentration of P and Mn. On the other hand, it increased the concentration of Ca, Mg, K and Zn. Thus, the application of charcoal residues in the substrate for the formation of seedlings should not be considered as a source of nutrients under the conditions of this work, but mainly as a soil physical conditioner. Under the conditions of this work, it is recommended to use only 20 t ha-1 of cattle manure in the composition of the substrate used for the production of faveira seedlings.
Keywords: Mudas - Produção; Adubos e fertilizantes orgânicos; Compostos orgânicos; CIENCIAS AGRARIAS; Enterolobium barnebianum; Material orgânico; Produção de mudas